Mutations in the Na+/Citrate Cotransporter NaCT (SLC13A5) in Pediatric Patients with Epilepsy and Developmental Delay - Jenna Klotz; Brenda E Porter; Claire Colas; Avner Schlessinger; Ana M Pajor (BMC, 2016)
Abstract Mutations in the SLC13A5 gene that codes for the Na+/citrate cotransporter, NaCT, are associated with early onset epilepsy, developmental delay and tooth dysplasia in children. In this study, we identify additional SLC13A5 mutations in nine epilepsy patients from six families. To better characterize the syndrome, families with affected children answered questions about the scope of illness and the treatment strategies. Currently, there are no effective treatments, but some antiepileptic drugs targeting the γ-aminobutyric acid system reduce seizure frequency. Acetazolamide, a carbonic anhydrase inhibitor and atypical antiseizure medication, decreases seizures in four patients. In contrast to previous reports, the ketogenic diet and fasting resulted in worsening of symptoms. The effects of the mutations on NaCT transport function and protein expression were examined by transient transfections of COS-7 cells. There was no transport activity from any of the mutant transporters, although some of the mutant transporter proteins were present on the plasma membrane. The structural model of NaCT suggests that these mutations can affect helix packing or substrate binding. We tested various treatments, including chemical chaperones and low temperatures, but none improved transport function in the NaCT mutants. Interestingly, coexpression of NaCT and the mutants results in decreased protein expression and activity of the wild-type transporter, indicating functional interaction. In conclusion, this study has identified additional SLC13A5 mutations in patients with chronic epilepsy starting in the neonatal period, with the mutations producing inactive Na+/citrate transporters.